ANALISIS KESALAHAN SISWA BERDASARKAN PROSEDUR NEWMAN PADA KEMAMPUAN KONEKSI MATEMATIS SISWA: Array - Ismunandar, Denni; Gunadi, Farid; Taufan, Mochammad Taufan3 (Universitas Peradaban, 2019)
The aims this research was to analysis students error using Newman Procedure. The subject this research is student of class in X MM1 SMKN 1 Balongan. Many sample were used by 6 student, consist of 2 students with lowest rank, 2 students with intermediate rank, and 2 students with high rank. The result of the analysis show that the average reading error is 38,86%, the average error in comprehension is 39,43%, the average transformation error is 34,86%, the average processing error is 52,57%, and the encoding error rate is 84,57%. Based on the result of the analysis of the six students, it can be concluded that students rarely write things that are know and asked and rarely write conclusion. This is what causes encoding to always win from the four previous stages.